The skills of competitive intelligence practitioners: complementing the cycle of competitive intelligence - Nur Izzati Mohamad Anuar,; Nik Malini Nik Mahdi; Nurul Hasliza Razmin,; Nur Dalila Mat Yusoff (International Business Information Management Association, 2013)
Essentially, this paper endeavours to explore the specific skills that would make up the skills sets for the competitive intelligence practitioners throughout the competitive intelligence phases for the product of competitive advantage. Thus, by outlining the competitive intelligence skills based on the competitive intelligence cycle, the readers will be served with a larger depiction of competitive intelligence in view of the fact that processes and activities cannot be conducted without prior existence of competencies and proficiencies.